2018
DOI: 10.1042/bsr20181116
|View full text |Cite
|
Sign up to set email alerts
|

XPG rs873601 G>A contributes to uterine leiomyoma susceptibility in a Southern Chinese population

Abstract: XPG gene contributes to DNA repair defects and genomic instability, which may lead to the initiation of uterine leiomyoma. We hypothesized that genetic variants of XPG gene may alter the carriers’ susceptibility to leiomyoma. The association between five potential functional single nucleotide polymorphisms (SNPs), i.e. rs2094258 C>T, rs751402 C>T, rs2296147 T>C, rs1047768 T>C, rs873601 G>A, and uterine leiomyoma risk in Chinese, was investigated in this case–control study, which included 398 incident leiomyoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previous studies reported that rs873601-AA was associated with some cancers, and XPG rs873601 AA increased the risk of glioma, 24 uterine leiomyoma, 25 and gastric cancer. 26 Our results extend susceptibility of rs873601 to lung cancer, however, rs873601 is not associated with NSCLC that may be due to the fact that most patients enrolled in the study were advanced cases at stage IV (67.4%) and their histological type concentrated on adenocarcinoma (73.2%).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies reported that rs873601-AA was associated with some cancers, and XPG rs873601 AA increased the risk of glioma, 24 uterine leiomyoma, 25 and gastric cancer. 26 Our results extend susceptibility of rs873601 to lung cancer, however, rs873601 is not associated with NSCLC that may be due to the fact that most patients enrolled in the study were advanced cases at stage IV (67.4%) and their histological type concentrated on adenocarcinoma (73.2%).…”
Section: Discussionmentioning
confidence: 93%
“…To date, there is limited available information regarding the potential inference of the NER pathway on the physiopathology of UF. A single report done in southern Chinese women has linked a higher susceptibility to UF with a single nucleotide polymorphism in XPG gene (rs873601 G > A), a crucial protein involved in NER repair processes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…If DNA repair fails, this damage can lead to carcinogenesis and tumor genomic instability [14]. Genetic and epigenetic aberrations in DNA damage repair pathway genes are associated with various pathogeneses [15][16][17][18][19][20][21][22]. These changes may be useful biomarkers in a liquid biopsy for the early detection and prevention of lung cancer.…”
Section: Introductionmentioning
confidence: 99%